Diagnostic Validity of the Generalized Anxiety Disorder - 7 (GAD-7) among Pregnant Women - Zhong, Qiu-Yue; Gelaye, Bizu; Zaslavsky, Alan M.; Fann, Jesse R.; Rondon, Marta B.; Sánchez, Sixto E.; Williams, Michelle A. (PLOS ONE, 2015)
Objective Generalized anxiety disorder (GAD) during pregnancy is associated with several adverse maternal and perinatal outcomes. A reliable and valid screening tool for GAD should lead to earlier detection and treatment. Among pregnant Peruvian women, a brief screening tool, the GAD-7, has not been validated. This study aims to evaluate the reliability and validity of the GAD-7. Methods Of 2,978 women who attended their first perinatal care visit and had the GAD-7 screening, 946 had a Composite International Diagnostic Interview (CIDI). The Cronbach’s alpha was calculated to examine the reliability. We assessed the criterion validity by calculating operating characteristics. The construct validity was evaluated using factor analysis and association with health status on the CIDI. The cross-cultural validity was explored using the Rasch Rating Scale Model (RSM). Results The reliability of the GAD-7 was good (Cronbach’s alpha = 0.89). A cutoff score of 7 or higher, maximizing the Youden Index, yielded a sensitivity of 73.3% and a specificity of 67.3%. One-factor structure of the GAD-7 was confirmed by exploratory and confirmatory factor analysis. Concurrent validity was supported by the evidence that higher GAD-7 scores were associated with poor self-rated physical and mental health. The Rasch RSM further confirmed the cross-cultural validity of the GAD-7. Conclusion The results suggest that the Spanish-language version of the GAD-7 may be used as a screening tool for pregnant Peruvian women. The GAD-7 has good reliability, factorial validity, and concurrent validity. The optimal cutoff score obtained by maximizing the Youden Index should be considered cautiously; women who screened positive may require further investigation to confirm GAD diagnosis.